2022
DOI: 10.1016/j.jesf.2021.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac autonomic disturbance following sprint-interval exercise in untrained young males: Does exercise volume matter?

Abstract: Objectives This study examined the influences of the volume of all-out sprint-interval exercise (SIE) on acute post-exercise heart rate variability (HRV) recovery. Methods HRV recovery following a session of (i) 2 × 30-s SIE (SIE 2 ), (ii) 4 × 30-s SIE (SIE 4 ), and (iii) non-exercising control (CON) were compared in 15 untrained young males. Time domain [standard deviation of normal-to-normal intervals, root mean sq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 38 publications
1
5
0
Order By: Relevance
“…In our study, the SIE protocol reduced HRV variables while increasing hemodynamic variables, which confirms our original hypothesis and the findings of previous studies [ 13 ]. For example, Stuckey et al (2011) and Ye et al (2022), demonstrated that SIE protocols (Wingate base) were associated with imposing significant stress on ANS and hemodynamic variables, which might lead to increased risk of cardiac events after these supramaximal exercises [ 9 , 13 ]. Previous studies have shown that vigorous exercise is associated with stimulation of sympathetic activation leading to increased catecholamine production [ 32 , 33 ].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In our study, the SIE protocol reduced HRV variables while increasing hemodynamic variables, which confirms our original hypothesis and the findings of previous studies [ 13 ]. For example, Stuckey et al (2011) and Ye et al (2022), demonstrated that SIE protocols (Wingate base) were associated with imposing significant stress on ANS and hemodynamic variables, which might lead to increased risk of cardiac events after these supramaximal exercises [ 9 , 13 ]. Previous studies have shown that vigorous exercise is associated with stimulation of sympathetic activation leading to increased catecholamine production [ 32 , 33 ].…”
Section: Discussionsupporting
confidence: 93%
“…Sprint interval exercise (SIE), because of its time efficiency and physiological benefits, has attracted much attention in the last decade among both healthy people and patients with chronic diseases such as obesity [ 10 , 11 , 12 ]. However, SIE might acutely cause an enhanced risk of cardiac events during exercise and the recovery period through overactivation of the sympathetic nervous system (SNS) and impairment of cardiac function and hemodynamic responses [ 9 , 13 ]. Stuckey et al (2012) compared cardiac autonomic and hemodynamic responses to single (one Wingate) and multiple sprint intervals (four bouts of Wingates) and found similar responses in HRV and hemodynamic variables; though, the recovery of HRV and hemodynamic variables took longer after four bouts compared to one bout [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kiviniemi considered this parasympathetic rebound period after prolonged exertion as the optimal training period for attaining cardiorespiratory adaptations; however, it may also lead to overreaching [ 32 ]. Based on these findings, many studies provided evidence in support of the usefulness of HRV recording during chronic exercise to optimize training adaptations and enhance gain in performance [ 12 , 49 ]. According to the results of our study, in line with Peçcanha et al [ 16 ] and Ballinger [ 8 ], vagal reactivation, reflecting in HRR, and vagal modulation, reflected in cPS cardiac indices and HR after exercise, could potentially reveal the difference between both possible scenarios; however, performance and fatigue are still proposed as major parameters distinguishing between both states [ 8 ], confirming the complexity of physiological mechanisms involved.…”
Section: Discussionmentioning
confidence: 99%
“…Parasympathetic reactivation after aerobic exercise also appears dependent on exercise modality with faster recovery following cycling than running as it involves a lower muscular activity (Cunha et al, 2015;Michael et al, 2017). In general, research findings regarding the acute effects of daytime or evening exercises at low-to-moderate intensity on cardiac autonomic modulation are mixed, with some studies reporting no alteration (Dias et al, 2021;Peçanha et al, 2014;Prodel et al, 2017;Yuda et al, 2018) and others showing decreases (Hynynen et al, 2010;Nie et al, 2022;Oda & Shirakawa, 2014;Ye et al, 2022;Yoshida et al, 2018) in HRV indices during the post-exercise recovery period. Dias et al (2021), for example, observed no differences in HRV indices expressed in natural logarithms in the rest period after a morning moderate-intensity ergometer cycling compared with a control condition in 11 sedentary young men.…”
mentioning
confidence: 99%